Vegetative growth of cowpea with alternative inoculant - Reis, Victor Roberto Ribeiro (2018)
The preparation of nodulated fine roots of cowpea is an alternative of inoculation with strains that perform the biological fixation of microbial community nitrogen locally adapted to the climatic and soil conditions, as well as to the local varieties. This work intends to evaluate the effect of inoculation from a fine root preparation on the vegetative growth of cowpea in comparison to commercial inoculation, urea fertilization and combinations thereof. The design was completely randomized with four replicates and the following treatments: T1: Witness; T2: Inoculum with roots; T3: Commercial inoculum; T4: Inoculum with roots + fertilization with urea in coverage; T5: Commercial inoculum + fertilization with urea under cover and T6: Fertilization with urea under cover. Root inoculation treatment plus cover nitrogen fertilization provided higher root length (57.25 cm) compared to treatment with only nitrogen fertilization in the cover (42.00 cm). In relation to the number of nodules at the 48 DAE, it was verified that the inoculation with roots was superior to the control and the nitrogenous fertilization in coverage. It was also observed that the SPAD index was lower in the control (40.25 g kg -1) and in urea fertilization (40.55 g kg -1). Fertilization with 20 kg ha-1 of urea resulted in lower root and shoot growth, number of nodules, dry mass of the plant part and SPAD index. The use of root inoculation is a viable alternative for the family farmer and agroecological based producers, but it needs to be evaluated in the field.